DISTRIBUTION AND BIO-PHYSICAL CHARACTERISTICS OF RESERVOIRS IN INDO-GANGETIC BASIN (IGB) IN RELATION TO THEIR FISHERIES - SARKAR, SANCHITA; KATIHA, PRADEEP K.; PAL, M. K. (Journal of the Inland Fisheries Society of India, 2021)
The reservoirs located in Indian IGB were assessed to establish relation between their bio-physical and institutional characteristics with fisheries management and fish yield. The analyses of information gathered from 521 IGB reservoirs revealed that i) >80% reservoirs had area <500 ha and their percentage decreased with increase in size; ii) fish seed stocked/ha and fish yield/ha also decreased with increase in area, iii) State Department of Irrigation (DoI) had the ownership of most (94%) of them with fisheries management responsibility with Department of Fisheries (DoF) iv) fishing effort had positive relationship with area of reservoirs, and v) fishing rights for most of the reservoirs (81%) were with contractor. Key words: Reservoirs, Indo-Gangetic basin, area, depth, fish yield, fishers, fishing, fishing rights